The Effort of ASEAN in Maintaining Cyber Threat in The Southeast Asia Region - Pasaribu, Batara Jeremy Chrisando (Jurnal Ilmiah Wahana Pendidikan, 2025)
Cybercrime has developed over a long period of time and is caused by the rapid development of globalization. All activities in the Southeast Asia region today are filled with technology, not only that, every ASEAN community has also participated in cyber developments. Southeast Asia is a region that is vulnerable to cybercrime due to the low level of security among ASEAN countries. This journal will discuss how and what ASEAN's efforts are to fight and overcome cybercrime which is growing rapidly in regions that are still developing, such as Southeast Asia.